A CORPUS-BASED ANALYSIS OF TRANSLATION STRATEGIES FOR CONNOTATIVE ENGLISH EPONYMS IN UZBEK. (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Connotative eponyms are a special class of proper nouns that have acquired metaphorical, evaluative, or symbolic meanings beyond their original reference. In English, these eponyms often derive from historical figures, literary characters, mythological heroes, or even contemporary personalities who have become widely recognized symbols of certain qualities or traits. For example, names such as Romeo connote a romantic lover, Scrooge denotes a miserly individual, and Einstein implies a person of exceptional intelligence. The connotative dimension of these eponyms presents significant challenges in translation, especially when the target language, in this case Uzbek,